PENGARUH GRIT TERHADAP JOB HOPPING PADA GENERASI Z KOTA BALIKPAPAN - Saputro, Edi; Dwi Nur Rahmah, Dian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The phenomenon of frequently changing jobs, commonly referred to as job hopping, began gaining widespread attention in 2023. This phenomenon can be detrimental to companies, as a lack of human resources may lower a company's performance. This study aims to examine the influence of grit on job hopping among Generation Z in Balikpapan City. This research uses a quantitative approach. The subjects of the study were 200 members of Generation Z in Balikpapan City, selected using purposive sampling. The data collection methods used were the job-hopping scale and the grit scale. The data analysis technique employed was simple regression. The collected data was processed using the SPSS program. The results of the study showed that grit has an effect on job hopping among Generation Z in Balikpapan City, with a p-value of 0.000 (p < 0.05), indicating that grit has a significant influence on job hopping. Grit affects job hopping among Generation Z in Balikpapan City with an R² value of 14.2%, which falls under the very low category. This research highlights the importance of considering grit in human resource management, especially among Generation Z. This study shows that it is important to pay attention to grit in HR management in order to reduce the intention to change jobs and support the stability of the workforce in the company. ABSTRAK Fenomena tentang suka berpindah-pindah pekerjaan ataau biasa disebut job hopping mulai ramai dibicarakan pada tahun 2023. Fenomena ini dapat merugikan suatu perusahaan dikarenakan kurangnya sdm dapat menurunkan performa suatu perusahaan. Penelitian ini bertujuan untuk mengetahui pengaruh grit terhadap job hopping pada generasi Z Kota Balikpapan. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek pada penelitian ini adalah 200 generasi Z Kota Balikpapan yang dipilih dengan menggunaakan purposive sampling. Metode pengumpulan data yang digunakan adalah skala job hopping dan skala grit. Teknik analisis data yang digunakan adalah regresi sederhana. Data yaang terkumpul diolah dengan bantuan program spss. Hasil penelitian menunjukkan bahwa terdapat pengaruh grit terhadap job hopping pada generasi Z Kota Balikpapan dengan nilai p = 0.000 (p < 0.05) yang berarti grit memiliki pengaruh yang signifikan terhadap job hopping. Grit mempengaruhi job hopping pada generasi Z Kota Balikpapan dengan nilai R2 sebesar 14.2% dengan kategori sangat rendah. Penelitian ini memperlihatkan bahwa pentingnya memperhatikan grit dalam pengelolaan SDM agar mengurangi intensi berpindah kerja dan mendukung stabilitas tenaga kerja di perusahaan.